(untitled) (Malaysian Journal of Civil Engineering, 2018)
This paper presents the preliminary result from a laboratory study to establish the moisture retention curve of undisturbed tropical peat samples classified as Sapric and Hemic. The results obtained were compared with those of the temperate peat. Under the same suction head, tropical peat seems to hold more water. The soil moisture at permanent wilting point (- 15000 cm or -150 kPa) was still relatively high at 50-60 % volumetric indicating that the soil was still visually wet, but may not be available for plant use. The possible implication could be, water table in the field should be maintained optimally high to facilitate irrigation water supply from capillary rise.